Single-Port Laparoscopic Surgery for Adnexal Mass Removal During Pregnancy: The Initial Experience of a Single Institute - Han, Ling; Wan, Qi; Chen, Yali; Zheng, Ai (Frontiers in Medicine, 2022)
Objective: Single-port laparoscopy has become a feasible and safe approach for the management of benign adnexal masses during pregnancy. To our knowledge, there are few reports on the feasibility and safety of single-port laparoscopy for adnexal mass removal during pregnancy. Our study reports the use of single-port laparoscopy in adnexal mass removal during pregnancy in our hospital. Methods: We included 10 cases of single-port laparoscopic surgery for adnexal Mass removal during pregnancy in West China’s Second University Hospital between January 2017 and March 2020. Median values were found using SPSS20. When the p value was <0.05 the median and interquartile range were used. All the patients agreed to this study. Results: The following median values were recorded: surgical time, 112.50 min; blood loss, 25 ml; postoperative hospital stay, 3 days; postoperative pain(visual analog scale [VAS]) at 6h, 3; and postoperative pain(VAS) at 24h, 2. Our study reported no postoperative spontaneous abortions. There was one preterm birth. Conclusion: Single-port laparoscopy appears to be safe for both the mother and the fetus.